Enhancing Students’ Vocabulary Mastery through Team Race Game: A Pre-Experimental Study - Sitti Aisa; Idayanti . (Prodi Pendidikan Bahasa Inggris, FKIP, LP3M Universitas Muhammadiyah Sidenreng Rappang, 2026)
This study examined whether the Team Race Game could enhance the vocabulary mastery of seventh-grade students at SMP Negeri 2 Panca Rijang. A quantitative pre-experimental approach with a one-group pretest-posttest design was employed. The population consisted of 99 seventh-grade students distributed across four classes in the 2018/2019 academic year, while Class VII.2, comprising 25 students, was selected through cluster sampling. Data were collected using a vocabulary pretest and posttest, classroom observation, and a 20-item interest questionnaire administered after the treatment. The intervention was implemented in four 80-minute meetings over two weeks. Descriptive statistics showed that the students’ mean score increased from 34.80 in the pretest to 67.16 in the posttest. The paired-sample t-test produced a significance value of 0.000, which was lower than the 0.05 significance level, indicating a statistically significant improvement after the treatment. The questionnaire results also revealed a mean interest score of 73.88; most students were categorized as interested in learning vocabulary through the game. These findings indicate that Team Race Game can provide an active, competitive, and enjoyable classroom environment that supports vocabulary practice and retention. The technique may therefore be used as an alternative strategy for teaching vocabulary in junior secondary EFL classrooms.